IMPLEMENTASI MODEL PROJECT BASED LEARNING BERBANTUAN LKS UNTUK MENINGKATKAN PENGUASAAN KONSEP FISIKA DAN PERFORMANCE SISWA (UPEJ Unnes Physics Education Journal, 2015)
The aim of this research is determining what the implementation of worksheet assisted Project Based Learning (PjBL) model can improve the physics concept mastery of dynamic fluid chapter and performances of student. The performances consist of the performance of group work, the performance of collecting data and the performance of oral presentation. This research used a quasi-experimental design by nonequivalent control group. The population was all of students of XI MIPA at SMA Negeri 1 Pecangaan while the sample was determined by purposive sampling technique with XI MIPA 1 as experimental group and XI MIPA 2 as control group. The results of research showed that the concept mastery of the experimental group could reach completeness of 78.79%. Based on gain test and t-test, concept mastery of the experimental group is better than the control group. Based on gain test of student’s performance, The performance of the experimental group is better than the control group. The conclusion of this research is the implementation of worksheet assisted PjBL model can improve the physics concepts mastery and performances of student.